2015
DOI: 10.1016/j.jopan.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Nurses' Attitudes Toward the Electronic Health Record

Abstract: Nursing acceptance and the utilization of the EHR are necessary for the successful integration of an EHR and to support the goal of patient-centered care. Identification of attitudes and potential barriers of perioperative nurses in using the EHR will improve patient safety, communication, reduce costs, and empower those who implement an EHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
57
6
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 16 publications
(30 reference statements)
12
57
6
7
Order By: Relevance
“…The questionnaire was developed by the researcher, guided by a review of related literature and survey instruments to assess levels of satisfaction with and perceived barriers to the EHR implementation identified in the literature . Multiple instruments were found in the literature and reviewed for content (domains and items).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was developed by the researcher, guided by a review of related literature and survey instruments to assess levels of satisfaction with and perceived barriers to the EHR implementation identified in the literature . Multiple instruments were found in the literature and reviewed for content (domains and items).…”
Section: Methodsmentioning
confidence: 99%
“…Registered nurses working in a 165‐bed urban hospital in the Southeastern USA reported that the EHR system improved communication among health‐care providers, contributed to time efficiency and better workflow, improved documentation quality and enhanced data completion and orders tracking . Perioperative nurses working in the Southeastern US health system perceived the EHR positively but did not believe it added significantly to workflow or improved documentation …”
Section: Introductionmentioning
confidence: 99%
“…The first category, EHR usability barriers and facilitators, is comprised of how easy the technology is to use, its functionality, ease of navigation and its impact on workload (Ammenwerth, Ehlers, Hirsch, & Gratl, ; Carayon et al., ; Carrington & Effken, ; Lu, Hsiao, & Chen, ; Maillet, Mathieu, & Sicotte, ; Saleem et al., ; Schenk et al., ; Whittaker, Aufdenkamp, & Tinley, ; Yontz, Zinn, & Schumacher, ). The second category, organizational context, includes: support from leadership, level of training, level of ongoing support and the physical environment (Lu et al., ; Maillet et al., ; Saleem et al., ; Whittaker et al., ; Yontz et al., ). The individual nurse characteristic category includes: sex, age, nursing unit, years of experience as a nurse, country of nursing education, years of experience using an EHR, previous experience using an EHR and formal informatics training (Ifinedo, ; Yontz et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…5 Nurses_ acceptance of EHRs has been studied in intensive care 6 and perioperative areas. 7 Investigators have compared nurse preference between EHRs and paper charts. 8,9 Several survey tools designed to assess various aspects of nurses_ attitudes toward EHR use are available.…”
mentioning
confidence: 99%